Pengaruh Kompres Hangat Terhadap Penurunan Skala Nyeri Pada Pasien Dengan Kolik Abdomen di Ruang Rawat Inap Rumah Sakit Lawang Medika - Qurrata Ayun, Sofa; Hidayati, Nurul; Fatmawati, Istiadah (LPPM STIKES HUSADA JOMBANG, 2022)
Breastfeeding problems can arise during childbirth and lactation are breast swelling, interventions to alleviate it is needed. Breast care spending could help smooth milk. Compress the cabbage leaves can be used for therapy because it helps widen the capillaries and increase blood flow to enter and exit, allowing the body to reabsorb the fluid that is unstoppable in the breast. The purpose of analyzing the effectiveness of the management and the cabbage leaf compress against breast swelling breast care for postpartum mothers. Type quasi experimental study design with non-randomized control group pretest posttest. Engineering samples of non-probability sampling types consecutive sampling. Total sample of 15 subjects per group. Pretest and posttest with SPES checklist. The experimental group intervention breastcare and compresses cabbage leaf, breastcare intervention control group. Intervention as 2x1 for 3 days. Results of analysis difference breast swelling scores before and after treatment between the experimental group compared with the control group gained Mann Whitney test p <0.001, and the value of Z -3306, 10.60 mean rank the experimental group and the control group mean rank 20,40. conclusion No difference difference in breast swelling scores before and after treatment was statistically significant between the experimental group than the control group in which cabbage leaf compress treatment and breast care more effectively address the problem of breast engorgement for postpartum mothers than breast care treatment only.